1996
DOI: 10.1046/j.1365-2443.1996.d01-259.x
|View full text |Cite
|
Sign up to set email alerts
|

The 12/23 rule is enforced at the cleavage step of V(D)J recombination in vivo

Abstract: Background: V(D)J recombination is initiated by the introduction of double-stranded breaks (DSB) adjacent to recombination signal sequences (RSS). Each RSS contains a conserved heptamer and a conserved nonamer element separated by a 12 or 23 nucleotide spacer. In vivo, efficient recombination requires one RSS of each spacer length, although it has been unclear whether this '12/23 rule' regulates cleavage, joining, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 38 publications
(73 reference statements)
7
31
0
Order By: Relevance
“…When lentiviruses carrying either a 12- or a 23-RSS were co-transduced into REH cells, so stimulation of RAG cleavage requires synapsis in trans , the amount of intact 12- and 23-RSS substrate was reduced to 70% and 74%, respectively, relative to samples where no partner is present (Figure 5A, left). This is consistent with the level of cutting previously published for cutting in trans using vectors with individual RSSs (Steen et al., 1996). When a SJ-carrying lentivirus is transduced with either a 12- or 23-RSS, in each case cutting occurs at the RSS, while negligible cleavage of the SJ is detected (Figure 5A).…”
Section: Resultssupporting
confidence: 92%
“…When lentiviruses carrying either a 12- or a 23-RSS were co-transduced into REH cells, so stimulation of RAG cleavage requires synapsis in trans , the amount of intact 12- and 23-RSS substrate was reduced to 70% and 74%, respectively, relative to samples where no partner is present (Figure 5A, left). This is consistent with the level of cutting previously published for cutting in trans using vectors with individual RSSs (Steen et al., 1996). When a SJ-carrying lentivirus is transduced with either a 12- or 23-RSS, in each case cutting occurs at the RSS, while negligible cleavage of the SJ is detected (Figure 5A).…”
Section: Resultssupporting
confidence: 92%
“…According to the current model, the RAG complex first binds to one RSS to form a signal complex (SC), which can recruit a partner RSS to form the paired complex (PC), also called the synaptic complex, in which double-strand breaks are generated between the coding gene segments and the RSSs810. While nicking can occur in both the SC and PC, hairpin formation is largely restricted to the PC and is sensitive to 12/23 synapsis8,1114. In the second phase of V(D)J recombination, the ends are processed and joined by proteins of the non-homologous end joining pathway15.…”
Section: Introductionmentioning
confidence: 99%
“…Recombination occurs only between gene segments where one segment is flanked by a 12-RSS and the other is flanked by a 23-RSS, a restriction known as the 12/23 rule. While the mechanisms underlying the 12/23 rule are poorly understood, the rule is enforced during the synapsis and hairpin formation steps (5,6,11,12). Gel shift experiments performed by Jones and Gellert (6) showed that the preference for 12/23 synapsis was stronger if the RAG proteins were incubated first with the 12-RSS than if they first saw the 23-RSS.…”
mentioning
confidence: 99%